Development of a battery-operated plasma device using dielectric barrier discharge plasma in ambient air - Khoi Nguyen Ho (2018)
Dielectric barrier discharge (DBD) plasma in air, a kind of non-thermal plasma, can disinfect the surface of a wound and enhance blood clotting without tissue damage. The purpose of this study was to design a prototype of a new, easily portable, DBD plasma device for first aid. In our prototype, the plasma discharge could be adjusted by changing frequency and using the pulse width modulation (PWM) function from a microcontroller. An electrode, coupled with the surface micro discharge (SMD) technique, reduced current leakage passing through the body. While the Lissajous standard method was utilized to measure the energy consumption per cycle, the optical emission spectroscopy approach analyzed the elements of plasma generation in ambient air. The prototype was convenient to carry and the amount of plasma discharge (containing the activated species O, OH, O2-, O3, N2, N2+) was easily varied to affect microorganisms and tissue.